Motivasi Pendidikan Orang Dewasa - Yanti Nurdiyanti; Ai Hilyatul Halimah (Universitas Negeri Makassar, 2020)
The need for rapidly changing work skills and demands for formal education qualifications are increasingly demanding for employees of the Government and Education agencies who have long worked with age over 30 years to upgrade themselves both in terms of skills and qualifications. This study aims to determine the source of motivation possessed by employees who have long worked with age over 30 years in improving education competency and qualification. This study uses a descriptive qualitative research method with the object of research in Sukamulya Village, Langkaplancar District, Pangandaran Regency, which carries out tertiary education at the Nahdlatul Ulama Tarbiyah College of Sciences, Al-Farabi Pangandaran. The results showed motivational sources from several sources in the most order as follows: 1) government policies towards fulfilling educational qualifications, 2) workplace intansi, 3) work systems 4) families 5) self-awareness to increase knowledge and skills in work